2001
DOI: 10.1016/s0022-5347(05)65547-4
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of Motor Urge Incontinence After Surgical Repair of Pelvic Organ Prolapse

Abstract: In most women with grade 2 or greater uterovaginal and coexistent motor urge incontinence urge incontinence resolved after the surgical repair of prolapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(36 citation statements)
references
References 6 publications
2
31
2
1
Order By: Relevance
“…Digesu et al [17] showed a significant improvement in overactive bladder symptoms after surgical repair of symptomatic anterior vaginal wall prolapse (stage ≥2) and a resolution of urge UI in 45% while Nguyen and Bhatia [18] reported a cure rate of 63% after surgical repair of uterine and/or vaginal vault prolapse compared to our cure rate of 33%. Milani et al on the other hand showed, in a study of vaginal repair with Prolene mesh, a high anatomical success rate of 93% with no change in urge or stress UI preoperatively and postoperatively [19] Although the relationship between stage of prolapse and bowel symptoms has been found to be weak [20,21], women with prolapse have been shown in a recent study to be more likely to suffer from difficult defaecation and faecal incontinence compared to matched controls [22].We found an improvement of difficulty in emptying bowels after traditional posterior colporrhaphy.…”
Section: Discussioncontrasting
confidence: 47%
“…Digesu et al [17] showed a significant improvement in overactive bladder symptoms after surgical repair of symptomatic anterior vaginal wall prolapse (stage ≥2) and a resolution of urge UI in 45% while Nguyen and Bhatia [18] reported a cure rate of 63% after surgical repair of uterine and/or vaginal vault prolapse compared to our cure rate of 33%. Milani et al on the other hand showed, in a study of vaginal repair with Prolene mesh, a high anatomical success rate of 93% with no change in urge or stress UI preoperatively and postoperatively [19] Although the relationship between stage of prolapse and bowel symptoms has been found to be weak [20,21], women with prolapse have been shown in a recent study to be more likely to suffer from difficult defaecation and faecal incontinence compared to matched controls [22].We found an improvement of difficulty in emptying bowels after traditional posterior colporrhaphy.…”
Section: Discussioncontrasting
confidence: 47%
“…In this study, we have shown significant improvement in these symptoms after anterior repair. Our findings extend and support previous studies [22,23] of the effect of surgical repair of grade 2 or more prolapse on symptoms of urge incontinence. The relationship between the severity of anterior wall prolapse and urinary symptoms is, however, far from clear.…”
Section: Discussionsupporting
confidence: 91%
“…Median parity was 2.5 (range 0-4) and body mass index 23 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Eleven women were premenopausal, 32 were on treatment with hormone replacement therapy preoperatively, and 114 (59%) were sexually active.…”
Section: Resultsmentioning
confidence: 99%
“…Quality-of-life measures also showed statistically significantly improvement at 12-month follow-up [30]. Nguyen and Bhatia [31] analyzed 38 women with grade 2 or greater POP (Baden-Walker system), all with DO on UDS along with symptomatic urgency incontinence, and reported a 63% resolution of urgency incontinence after POP repair, including both abdominal and vaginal reconstruction. Again, patients undergoing antiincontinence procedures were excluded.…”
Section: Surgical Repair Of Pelvic Organ Prolapsementioning
confidence: 99%
“…Lower amplitude of uninhibited detrusor contraction on UDS preoperatively and presence of bladder trabeculation on cystoscopy were correlated with resolution of urge incontinence. Four patients who were subjectively "improved" but did not report symptoms as "resolved" were grouped with persistent urge incontinence, possibly diluting the positive impact of repair [31]. Crafoord et al [32] surveyed 188 patients for pelvic floor dysfunction who had undergone POP repair a mean 5.9 years prior to the questionnaire.…”
Section: Surgical Repair Of Pelvic Organ Prolapsementioning
confidence: 99%